Urgensi 'social capital' dalam revitalisasi organisasi kemahasiswaan di Universitas Negeri Yogyakarta - Nasiwan Nasiwan (Jurnal Civics: Media Kajian Kewarganegaraan, 2009)
Social capital plays an urgent role in building and maintaining elan vital of student bodies which are up to some level fragmented into subcomponent labels and step down into internal frictions. The social capital should emerge and be maintained in any activity of students organizations and interrelation among them. Student boards and also lecturers should have conscious ness to raise and increase the social capital.